2006
DOI: 10.3354/dao068251
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in four mitochondrial genes of the salmon louse Lepeophtheirus salmonis

Abstract: A total of 210 Lepeophtheirus salmonis collected from 7 locations (Scotland, Russia, Canada, Japan and 3 locations in Norway), were screened for sequence variation in 4 mitochondrial genes; ATPase subunit 6 (A6), Cytochrome b oxidase subunit I (COI ), Cytochrome b (Cyt b) and 16S rRNA. A high level of intraspecific variation was observed within all genes. The majority of polymorphisms were present in single individuals only, which resulted in a high number of private haplotypes within each gene. Little evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 58 publications
5
48
3
Order By: Relevance
“…The population genetic structure of Lepeophtheirus salmonis has been subject to several investigations throughout the Atlantic. Tentatively, previous studies can be divided into those which have revealed weak (Tjensvoll et al 2006) or no (Todd et al 2004) population genetic structure, and those revealing significant levels of genetic differentiation, sometimes over very short distances (Dixon et al 2004, Nolan & Powell 2009). To varying degrees, previous studies may be subject to technical and sampling limitations, and results may be difficult to compare between marker classes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The population genetic structure of Lepeophtheirus salmonis has been subject to several investigations throughout the Atlantic. Tentatively, previous studies can be divided into those which have revealed weak (Tjensvoll et al 2006) or no (Todd et al 2004) population genetic structure, and those revealing significant levels of genetic differentiation, sometimes over very short distances (Dixon et al 2004, Nolan & Powell 2009). To varying degrees, previous studies may be subject to technical and sampling limitations, and results may be difficult to compare between marker classes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the samples were collected on fish as they were slaughtered, while other samples were taken in association with routine lice-counting on farms. As large genetic differences between L. salmonis in the Pacific and Atlantic have previously been well documented (Todd et al 2004, Tjensvoll et al 2006, Yazawa et al 2008, no outlier sample from the Pacific was included. For Canada, Ireland, Shetland and the Faroe islands, 2 samples country -1 were collected.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Plankton sampling discovered higher densities of L. salmonis copepodites in very shallow water along the seashore and in estuarine areas of Ireland and Scotland (Costelloe et al 1995(Costelloe et al , 1998McKibben & Hay 2004). While the same copepodite distribution may be expected in British Columbia, it requires confirmation because the Pacific and Atlantic populations of L. salmonis are genetically distinct (Tjensvoll et al 2006;Todd et al 2006) and may have different evolutionary adaptations. Thus, at least in Europe, empirical data indicated that the infective copepodites of L. salmonis concentrated in the path of migrating salmonids in estuaries.…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%